2022
DOI: 10.24996/ijs.2022.63.9.14
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Some Heavy Metals and Radioactivity in the Dust in A Selected Area in Kirkuk Governorate- Northern Iraq

Abstract: Air pollution means the release of pollutants into the atmosphere, which are harmful to human health and the planet as a whole. Almost all air pollutants come from production and energy use. In the present work, an assessment of some heavy metals, natural radioactivity and the quantity of dust fallen in three sites (Tessen, Rahemawa, and Laylan) in Kirkuk Governorate, northern Iraq. Three dust samples were collected from three locations (residential, commercial and industrial areas). The collected samples were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
0
1
Order By: Relevance
“…The mean concentration values for each heavy metal are shown in Table 1. The Cu mean value of 49.520 mg/L in the current study's data was found to be the highest and much higher than that in earlier reference studies conducted in Iraq (Kadhum, 2020;Khwedim et al, 2022)). The Cr, Ni, and Pb levels were greater than those found in the cited research.…”
Section: Heavy Metal Levels In Outdoor Aerosolscontrasting
confidence: 82%
“…The mean concentration values for each heavy metal are shown in Table 1. The Cu mean value of 49.520 mg/L in the current study's data was found to be the highest and much higher than that in earlier reference studies conducted in Iraq (Kadhum, 2020;Khwedim et al, 2022)). The Cr, Ni, and Pb levels were greater than those found in the cited research.…”
Section: Heavy Metal Levels In Outdoor Aerosolscontrasting
confidence: 82%
“…The wide utilization of paints, fertilizers, and gazes emissions from factories within the studies area could be a source of Cd [30]. Many contaminant resources may be added and cause an increment in heavy metal values within the Erbil province, like oil industries, fuel burning in different kinds of cars, and high traffic intensity [31].…”
Section: Discussionmentioning
confidence: 99%